Developing Organizational Citizenship Behaviour: Organizational Climate and Leader-Member Exchange Effects - Hemaloshinee, Vasudevan A.; Imran, Aslan (Sumy State University, Ukraine, 2022)
Supervisory behaviour has influenced a better working climate, which has led to the employees' desire to achieve a favourable outcome for the business involved. If the leaders do not contribute constructive behaviour, the staff may desire a poor outcome. Banks were chosen because they participate in a high-quality endeavour to build leader-member exchange relationships among workers. By examining employees' citizenship behaviour, the findings of this study could be used to improve the quality of leader-member exchange and the work environment. An effective organizational climate must incorporate the leader-member exchange strategy to improve employees' working environments, leaders-followers relationships, and employees' citizenship behaviour. The importance of this study is to determine that organizational climate is a visible value that has been in existent within the employee's behaviour and action. This study aims to assess the mediating role of the organizational climate on the relationship between leader-member exchanges on organizational citizenship behaviour. Reviewing underpinning theories based on underlying concepts, theoretical background, current definitions, and various types of collaborative writing gathered from the educational setting resulted in a theoretical framework. The quantitative and purposive sampling methods have been used to achieve the research questions and hypothesis. Samples were taken that amounted to 384 respondents in the commercial banks, Kuala Lumpur, Malaysia. Descriptive statistics analysed the variables, correlation and Structural Equation Modelling (SEM) using IBM Statistical Package for Social Sciences (SPSS) and SMART PLS 3. Findings of this study reveal that organizational climate has a positive relationship with significant levels on the leader-member exchange and organizational citizenship behaviour. This study suggests that it be pursued further in the Asian and Western contexts due to the development of organizational citizenship behaviour. Because it is fundamental for many organizations to develop their company profile to achieve good changes so that human resource management is strategized in the hiring and retaining system for highly committed employees to organizations